Feminine capital : unlocking the power of women entrepreneurs - Orser, Barbara; Elliott, Catherine (Stanford, California : Stanford Business Books, an imprint of Stanford University Press, 2015)
Today, there are over 200,000,000 women business owners around the world. Many of these entrepreneurs are not doing business as usual, nor are they simply leaning in. Rather, they are tapping into feminine capital-the unique skills and sensibilities that they have cultivated as women-to create enviable successes. Drawing on four decades of award-winning research, Feminine Capital reveals how women are harnessing different approaches to doing business. Barbara Orser and Catherine Elliott detail the pillars of feminine capital and offer new insight into the ways that gender can influence entrepre.
Reframing entrepreneurship -- Intention, success, and identity -- Getting to go -- Enterprise growth -- Social capital -- Money matters -- Power in policy -- Never underestimate the underestimated woman.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO; viewed on March 5, 2015).
English.
Keywords: Businesswomen; Women-owned business enterprises; Self-employed women; Entrepreneurship; BUSINESS & ECONOMICS -- Industries -- General; Businesswomen; Entrepreneurship; Self-employed women; Women-owned business enterprises; Unternehmerin; Entrepreneurship; Electronic books; Electronic books